2021
DOI: 10.2174/2211536610666210506125036
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of MicroRNA-15a and MicroRNA-16-1 Salivary Level in Oral Squamous Cell Carcinoma Patients

Abstract: Background: Squamous Cell Carcinoma (SCC) includes more than 90% of malignancies of the oral cavity. Early diagnosis could effectively improve patients' quality of life and treatment outcomes of oral cancers. MicroRNAs as non-encoding genes have great potential to initiate or suppress cancer progression. Recent studies have shown that disruption of micro-RNA regulation is a common occurrence in cancers. Objective: This study set out to evaluate the expression of microRNA-15a (miR-15a) and microRNA-16-1 (miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In OSCC tissues, miR-16 is markedly decreased compared to adjacent non-cancerous tissues [ 273 , 274 , 275 ]. Salivary miR-16 levels are also downregulated in patients with OSCC [ 276 ]. Notably, miR-16 expression is downregulated in patients with metastatic oral cancer and a more advanced TNM stage [ 162 , 273 ], and it is associated with poor overall survival; therefore, it could be used as a robust prognostic biomarker [ 162 ].…”
Section: The Role Of the Most Common Mirnas In Hncmentioning
confidence: 99%
“…In OSCC tissues, miR-16 is markedly decreased compared to adjacent non-cancerous tissues [ 273 , 274 , 275 ]. Salivary miR-16 levels are also downregulated in patients with OSCC [ 276 ]. Notably, miR-16 expression is downregulated in patients with metastatic oral cancer and a more advanced TNM stage [ 162 , 273 ], and it is associated with poor overall survival; therefore, it could be used as a robust prognostic biomarker [ 162 ].…”
Section: The Role Of the Most Common Mirnas In Hncmentioning
confidence: 99%
“…In contrast, miR-16-1 showed a sensitivity and speci city of 86.67% and 92.33%, respectively. miR-15a shows more sensitivity than our miRNA signature in discriminating OSCC from controls, which may be due to the low sample number recruited in their study 20 . Similarly, Romani et al reported that a panel of miR-106-5p, miR-423-5p, and miR-193b was able to distinguish OC (n = 55) from healthy controls (n = 39) with an AUC of 0.98, sensitivity of 97.4% and speci city of 94.2%.…”
Section: Discussionmentioning
confidence: 80%
“…miR-15a shows more sensitivity than our miRNA signature in discriminating OSCC from controls, which may be due to the low sample number recruited in their study. 22 Similarly, Romani et al reported that a panel of miR-106-5p, miR-423-5p, and miR-193b was able to distinguish OC ( n = 55) from healthy controls ( n = 39) with an AUC of 0.98, sensitivity of 97.4% and specificity of 94.2%. Their study considered only the upregulated miRNAs, whereas we included both upregulated and downregulated ones to eliminate bias in selecting biomarkers.…”
Section: Discussionmentioning
confidence: 93%